Letters from Tunisia: Darwish and the Palestinian State of Mind. Issue 1 (April 2015) - Brennan, Timothy
<x xml:space="preserve">Abstract</x> In this timely and engaged contemplation of the 'Palestinian state of mind', Timothy Brennan takes his cue from a personal experience of the imperviousness of liberal interdisciplinary academia in 'parochial America' towards Arab and Islamic culture. This leads to a longer reflection on the persistent network of Western power today, which, having mediated the recent Arab uprisings to its own ends, continues to sustain in myriad forms an oppressive order that cripples the Palestinian effort towards self-determination. In incisive readings of poems by two seminal Palestinian poets, Mahmoud Darwish and Mourid Barghouti, Brennan explores the fraught distance between the sense of 'crushing understatement' in these works: an emotional tenor that is inherently premised both on its readers' will to honour its meanings and its embattled operation within, in Brennan's words, 'the disarticulation of a people'. In this light, Brennan's essay moves to address the unintended ironies inherent in the term 'postcolonialist critique' as it encompasses 'the metallic reality of an extravagant contemporary colonialism'. He criticises the complicity of postcolonial studies in exacerbating rather than facilitating 'the difficulty of reading peripheral value', as well as its entrenched reluctance to interrogate imperialism. In the final part of his essay, Brennan advocates attunement to the political address of the aesthetics of the periphery. This as an exercise that, in refusing to rely on the tropes of a compromised literary modernism, seeks to access that 'very physical presence of the bodies of a collectivity in speech' within the literature of the periphery that – like the Palestinian state of mind itself – has been hitherto disparaged by Eurocentric protocols of reading. In the process, and throughout, the paper provides ample reflection on the affinities between the countertextual and critical practice within postcolonial studies.